Taxonomic notes on the genus Gonycentrum Bergroth (Hemiptera: Tingidae) - Lis, Barbara; Lis, Jerzy A. (Zootaxa, 2006)
The monotypic phatnomatine genus Pampacader (with its single species P. cicchinoi) was recently described from Argentina (Carpintero & Montemayor 2005) as the first genus of the tribe Phatnomatini recorded from Buenos Aires province and the third (after Phatnoma Fieber and Eocader Drake & Hambelton) known from Argentina. The genus was then soon compared with Ambarcader Perrichot, Nel, Guilbert & Néraudeau, described from the Lower Cretaceous amber of France, in a discussion of the systematic position of this new fossil genus within the family (Perrichot et al. 2006).